9(x+5)-(4x-1)=8

Simple and best practice solution for 9(x+5)-(4x-1)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+5)-(4x-1)=8 equation:


Simplifying
9(x + 5) + -1(4x + -1) = 8

Reorder the terms:
9(5 + x) + -1(4x + -1) = 8
(5 * 9 + x * 9) + -1(4x + -1) = 8
(45 + 9x) + -1(4x + -1) = 8

Reorder the terms:
45 + 9x + -1(-1 + 4x) = 8
45 + 9x + (-1 * -1 + 4x * -1) = 8
45 + 9x + (1 + -4x) = 8

Reorder the terms:
45 + 1 + 9x + -4x = 8

Combine like terms: 45 + 1 = 46
46 + 9x + -4x = 8

Combine like terms: 9x + -4x = 5x
46 + 5x = 8

Solving
46 + 5x = 8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-46' to each side of the equation.
46 + -46 + 5x = 8 + -46

Combine like terms: 46 + -46 = 0
0 + 5x = 8 + -46
5x = 8 + -46

Combine like terms: 8 + -46 = -38
5x = -38

Divide each side by '5'.
x = -7.6

Simplifying
x = -7.6

See similar equations:

| 15+35x= | | 4x+2x-2=6x-3+1 | | -4cosx-3sinx=2 | | 3-n-4n=-2 | | 6t^2+18t+12=0 | | [y-5]=3[x+2] | | 0n+4n+1=17 | | 5(2x-7)=7x+3x+7 | | -5=8f+11 | | (10b-1)-3(3b+1)=-4 | | 4x+5-6=3(x+3) | | -16=4/3x-8 | | 2c-5=-5c+9 | | 3=4-3n+4n | | 15+3y=-9 | | 4x+6+10x-1+3x+6=360 | | 5-3x=-3x+8 | | 0=0.03x^2-1.2x+2 | | 4.25/0.5 | | [y+11]=-7[x-2] | | (9x^2+2x+3)-(4x^2+3x+-7)= | | -4x-4.1=11.02 | | 7.3y-5-18=-51.9 | | -2-4x=2(1-3x) | | 5/2t=1/2 | | 7/2t=1/2 | | -y=y+10 | | 6+8x=40 | | 32x^2-40x^5= | | =|3 | | 4/6k=1/6 | | M-(24)=41 |

Equations solver categories